X-Ray and Multiwavelength Polarization of Mrk 501 from 2022 to 2023 - Chen, Chien-Ting J.; Liodakis, Ioannis; Middei, Riccardo; Kim, Dawoon E.; Di Gesu, Laura; Di Marco, Alessandro; Ehlert, Steven R.; Errando, Manel; Negro, Michela; Jorstad, Svetlana G.; Marscher, Alan P.; Wu, Kinwah; et al. (Institute of Physics Publishing, 2025)
We present multiwavelength polarization measurements of the luminous blazar Mrk 501 over a 14 month period. The 2–8 keV X-ray polarization was measured with the Imaging X-ray Polarimetry Explorer (IXPE) with six 100 ks observations spanning from 2022 March to 2023 April. Each IXPE observation was accompanied by simultaneous X-ray data from NuSTAR, Swift/XRT, and/or XMM-Newton. Complementary optical–infrared polarization measurements were also available in the B, V, R, I, and J bands, as were radio polarization measurements from 4.85 GHz to 225.5 GHz. Among the first five IXPE observations, we did not find significant variability in the X-ray polarization degree and angle with IXPE. However, the most recent sixth observation found an elevated polarization degree at >3σ above the average of the other five observations. The optical and radio measurements show no apparent correlations with the X-ray polarization properties. Throughout the six IXPE observations, the X-ray polarization degree remained higher than, or similar to, the R-band optical polarization degree, which remained higher than the radio value. This is consistent with the energy-stratified shock scenario proposed to explain the first two IXPE observations, in which the polarized X-ray, optical, and radio emission arises from different regions.